On the performance of two‐user full‐duplex network‐coded cooperation. (5th March 2019) - Mafra, Samuel B.; Fernández, Evelio M. G.; Montejo‐Sánchez, Samuel; Souza, Richard D.; Rayel, Ohara K.; Rebelatto, João L.
Summary: In this paper, we propose two schemes based on a full‐duplex network‐coded cooperative communication (FD‐NCC) strategy, namely, full‐duplex dynamic network coding (FD‐DNC) and full‐duplex generalized dynamic network coding (FD‐GDNC). The use of full‐duplex communication aims at improving the spectrum efficiency of a two‐user network where the users cooperatively transmit their independent information to a common destination. In the proposed FD‐NCC schemes, the self‐interference imposed by full‐duplexing is modeled as a fading channel, whose harmful effect can be partially mitigated by interference cancellation techniques. Nevertheless, our results show that, even in the presence of self‐interference, the proposed FD‐NCC schemes can outperform (in terms of outage probability) the equivalent half‐duplex network‐coded cooperative (HD‐NCC) schemes, as well as traditional cooperation techniques. Moreover, the ϵ ‐outage capacity, that is, the maximum information rate achieved by the users given a target outage probability, is evaluated. Finally, we examine the use of multiple antennas at the destination node, which increases the advantage of the FD‐NCC (in terms of the diversity‐multiplexing trade‐off and ϵ ‐outage capacity). Abstract : In this paper, we propose two schemes based on a full‐duplex network‐coded cooperative communication (FD‐NCC) strategy, namely, full‐duplex dynamic network coding (FD‐DNC) and full‐duplex generalized dynamic network coding (FD‐GDNC), for a scenario with multiple antennas at the destination node. We evaluate the proposed schemes in terms of outage probability, diversity‐multiplexing trade‐off, and ϵ ‐outage capacity. Even in the presence of self‐interference, the proposed FD‐NCC schemes can outperform the equivalent half‐duplex network‐coded cooperative (HD‐NCC) schemes, as well as traditional cooperation techniques.